2016
DOI: 10.2967/jnumed.115.167825
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetic Modeling and Dosimetry for Optimizing Intraperitoneal Radioimmunotherapy of Ovarian Cancer Microtumors

Abstract: A biokinetic model was constructed to evaluate and optimize various intraperitoneal radioimmunotherapies for micrometastatic tumors. The model was used to calculate the absorbed dose to both anticipated microtumors and critical healthy organs and demonstrated how intraperitoneal targeted radiotherapy can be optimized to maximize the ratio between them. Methods: The various transport mechanisms responsible for the biokinetics of intraperitoneally infused radiolabeled monoclonal antibodies (mAbs) were modeled us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 20 publications
(22 reference statements)
0
33
0
Order By: Relevance
“…The significantly greater sensitivity of the cells (three- to forty-fold) to a targeted RIC relative to a control RIC in these studies is equivalent to or greater than those reported for other cancer cells and radionuclides [16, 42-45]. The in vitro IC 50 concentrations of 212 Pb-376.96 against adherent ovarian cancer cells and CICs (1.6-33 kBq/mL) were lower than the maximum concentrations of alternative α-particle RICs calculated to be present in the peritoneum of ovarian cancer patients (42-100 kBq/mL) during clinical trials [15, 19, 21]. This demonstrates the utility of 212 Pb-376.96 at clinically achievable concentrations to kill both differentiated cells and CICs that promote metastases, chemoresistance, and recurrent disease.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The significantly greater sensitivity of the cells (three- to forty-fold) to a targeted RIC relative to a control RIC in these studies is equivalent to or greater than those reported for other cancer cells and radionuclides [16, 42-45]. The in vitro IC 50 concentrations of 212 Pb-376.96 against adherent ovarian cancer cells and CICs (1.6-33 kBq/mL) were lower than the maximum concentrations of alternative α-particle RICs calculated to be present in the peritoneum of ovarian cancer patients (42-100 kBq/mL) during clinical trials [15, 19, 21]. This demonstrates the utility of 212 Pb-376.96 at clinically achievable concentrations to kill both differentiated cells and CICs that promote metastases, chemoresistance, and recurrent disease.…”
Section: Discussionmentioning
confidence: 95%
“…The trend of prolonged mouse survival with higher doses of 212 Pb-376.96, coupled with the finding that all mice eventually succumbed to disease burden, suggests that in vivo saturation of the target epitope had not occurred with the doses used here [47]. Microdosimetry calculations and experimental results indicate that administering α-particle RICs in high specific activity at doses that saturate the target epitope in vivo is a viable strategy to maximize the absorbed dose to tumors without significantly increasing the dose to normal tissues [15, 49]. The significantly prolonged survival of mice that received 212 Pb-376.96 relative to a comparable dose of 212 Pb-F3-C25 demonstrates the advantage of targeting the mAb-defined B7-H3 epitope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful preclinical studies with 211 At have already led to a clinical phase I study [10, 11], and additional clinical trials are planned. While most of our efforts have been spent on development and evaluation of 211 At radiopharmaceuticals, model calculations [12] show that 213 Bi might be preferential for intraperitoneal (i.p.) radioimmunotherapy (RIT) of disseminated ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, a huge amount of effort has been invested in the creation of dosimetric algorithms to analyze dose deposition and dose–response in clinical and preclinical models. Some of these models are based on theoretical calculations that make educated assumptions about source deposition [811], while others use nuclear imaging methods such as single photon emission computed tomography (SPECT) to approximate the source distribution [4, 5, 12]. Although theoretical models can help one quickly change parameters and estimate outcomes, the calculated distributions do not represent the actual heterogeneity of source and dose distribution in a tumor.…”
Section: Introductionmentioning
confidence: 99%